If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 = 7(y + -5) Reorder the terms: -14 = 7(-5 + y) -14 = (-5 * 7 + y * 7) -14 = (-35 + 7y) Solving -14 = -35 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -14 + -7y = -35 + 7y + -7y Combine like terms: 7y + -7y = 0 -14 + -7y = -35 + 0 -14 + -7y = -35 Add '14' to each side of the equation. -14 + 14 + -7y = -35 + 14 Combine like terms: -14 + 14 = 0 0 + -7y = -35 + 14 -7y = -35 + 14 Combine like terms: -35 + 14 = -21 -7y = -21 Divide each side by '-7'. y = 3 Simplifying y = 3
| -2=7-v | | 7-2a=54 | | 10+e-5+e=5(e-1) | | -7/2-3/7x=-8/3 | | 4x^2=-28x | | 3(u+6)=7u | | 9y-8y=12 | | x-4-1=7 | | 2x^2+13x-30=0 | | 4(13n+4)=-36 | | 3u+30=-3(u+6) | | 5.6-2a+1.4=54 | | (8j-3l+9)6= | | 2(6-y)-7y=-7 | | (6+w)(5w+3)=0 | | 4t+5=3t+5+t | | z^2+13z=-42 | | 33x=3x^2-7x-18 | | .7(v+3.2)=-.28 | | -14x^2+54x-36=0 | | 3-x(x-5)=5 | | 24k^2-31k-36=k | | 0.6(x-1.3)=.15 | | 27-4t-12t=t-7 | | X^2-5x-29=0 | | 12x+3x=100+22 | | 64=((2*h)*h)/2 | | 5x+5x=70 | | x^2-6-5x=0 | | -8m-3m=16 | | 64=(2h*h)/2 | | 7(4n-5m)= |